Lablab (Dolichos lablab) meal as protein supplement for weaned fattening lambs - Mafwere, W.D.; Mtenga, L.A. (1992)
A study was conducted to investigate the effect of inclusion of Lablab meal on growth rate, feed intake and carcass composition of Black Head Persian (BHP) lambs. Twenty-four BHP castrate sheep with average weight of 14.1 +2.7 kg were allotted randomly to four dietary treatments. Lambs were individually maintained in metabolic crates. All animals were offered hay ad libitum. Lambs on control treatment (A) were given in addition 380 g of maize bran per day. Animals on treatments B. C, and D were given daily 380 g of concentrate based on maize bran with 25,50 and 75% lablab meal, respectively.Growth rate, dry-matter intake and feed conversion ratio were 34,66, 68, 71 g/day; 58.7,69.5, 74.0 g/kgW0.75/day and 15.2,11.3,9.3,9.1 g/DMI/g gain, respectively, of treatments A, B. C and D. The level of inclusion of lablab meal had no significant (P>0.05) effect on killing-out characteristics. Hot carcass weight as percentages of slaughter weight and empty body weight were 41.3,41.0,40.5,42.5 and 52.0,52.3,53.5, respectively, for animals on treatments A, B. C and D. Carcass composition expressed as percentage of carcass weight showed no significant treatment effects and value of 60.91, 61.29, 61.11 and 62.97% for carcass lean, 19.06,20.24, 18.42 and 17.54% carcass fat and 17.86,16.70,17.91 and 16.67% for carcass bone were obtained for treatments A, B. C and D. It is concluded that inclusion of lablab meal in maize bran above 25% has no beneficial effect in terms of growth rate and carcass composition.